COLLABORATIVE GAMING APPROACH IN ONLINE LEARNING TO IMPROVE STUDENTS’ ENGAGEMENT - Anita Carolin; Alies Poetri Lintangsari (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Due to the COVID-19 pandemic, students in Indonesia were required to study from home for about the past two years. It affected learning activities that made students less engaged. This research offers the Online Collaborative Gaming Approach model to improve students’ engagement and participation in English learning. Inviting 58 students as research participants, the researchers reported the implementation of the Collaborative Gaming Approach and evaluation based on students’ perspectives. This study employed Classroom Action Research utilizing students’ scores, questionnaires and interviews, to measure the criteria of success. The result of the study showed that the average score in the quiz game activity inceased after the implementation of the quiz game (from 74,1 to 88,64). The result of the questionnaires also stated that 94.83% (55) students agreed that quiz game activities gave positive perceptions on the affective aspect, 91.38% (53) students agreed that quiz game activities gave positive perceptions on the social aspect, and 94.83% (55) students agreed that quiz game activities gave positive perceptions on the cognitive aspect. The result of the data showed that the collaborative gaming approach gives a positive impact on students. It implies that the practice of the collaborative gaming approach can increase the students’ engagement.